Dakwah dan Pemberdayaan Masyarakat Berbasis Agama - Rahmat Ramdhani (JURNAL ILMIAH SYI'AR, 2018)
The concept of religious-based community empowerment can be said that the preaching of development seeks to carry out its mission to improve the quality of life of the community, physically and mentally. The effort to improve the quality of life of the community is carried out by bringing them to an Islamic life, by increasing their faith and devotion and their ability to master technology. With the superiority of this body and spirit, the aspiration towards a just, prosperous and inner and prosperous society can be achieved. With this preaching empowerment effort, it has relevance and is in line with the mission of spreading Islam, which is to bring mercy to the universe. Learning from the process of spreading Islam, the process of preaching empowerment should begin on the basis of religion which is then associated with an understanding of various natural phenomena and social problems, all of which are considered as a whole. In the framework of this religious mission, community development is carried out to make a prosperous and inner society. This process is carried out using a pilot model method, which starts with the personal Da'i which is then extended to small environmental communities which are then developed and expanded